Amniotic Membrane Extract Protects Islets From Serum-Deprivation Induced Impairments and Improves Islet Transplantation Outcome - Yang, Zhaoming; Li, Xiaohang; Zhang, Chengshuo; Sun, Ning; Guo, Tingwei; Lin, Jianzhen; Li, Feng; Zhang, Jialin (Frontiers in Endocrinology, 2020)
Islet culture prior to transplantation is a standard practice in many transplantation centers. Nevertheless, the abundant islet mass loss and function impairment during this serum-deprivation culture period restrain the success of islet transplantation. In the present study, we used a natural biomaterial derived product, amniotic membrane extract (AME), as medium supplementation of islet pretransplant cultivation to investigate its protective effect on islet survival and function and its underlying mechanisms, as well as the engraftment outcome of islets following AME treatment. Results showed that AME supplementation improved islet viability and function, and decreased islet apoptosis during serum-deprived culture. This was associated with the increased phosphorylation of PI3K/Akt and MAPK/ERK signaling pathway. Moreover, transplantation of serum-deprivation stressed islets that were pre-treated with AME into diabetic mice revealed better blood glucose control and improved islet graft survival. In conclusion, AME could improve islet survival and function during serum-deprived pretransplant culture and promote graft outcome following islet transplantation, and was at least partially through increasing phosphorylation of PI3K/Akt and MAPK/ERK signaling pathway.